Investment determinants of young and old Portuguese SMEs: A quantile approach - Silvia Mendes; Zélia Serrasqueiro; Paulo Maç\~as Nunes (BRQ Business Research Quarterly, 2014)
Considering two samples of Portuguese SMEs: 582 young SMEs and 1654 old SMEs, using the two-step estimation method and quantile regressions, the empirical evidence allows us to conclude that the determinants of investment have a different impact on young and old SMEs, depending on a firm' level of investment. In the framework of Acceleration Principle and Neoclassical Theories, the determinants are relevant in explaining the investment of young and old SMEs with high levels of investment. The Growth Domestic Product, as the investment determinant of Acceleration Principle Theory, has a greater impact on the investment of young SMEs with high levels of investment. Sales, as the investment determinant of Neoclassical Theory, have greater impact on the investment of old SMEs with high levels of investment. Cash flow, as the investment determinant of Free Cash Flow Theory, is important in explaining the investment of young and old SMEs with low levels of investment. However, cash flow has greater impact on the investment of young SMEs with low levels of investment. The empirical evidence obtained allows us to make suggestions for policy-makers and the owners/managers of Portuguese SMEs."
Keywords: 650; Investment; Old SMEs; Quantile regressions; Young SMEs